Kinetics of the Degradation of n-Butyl Benzyl Phthalate using O3/UV. Direct Photolysis, Direct Ozonation and UV Effects - Lovato, Maria Eugenia (2015)
The aim of this work is to study the degradation kinetics of the endocrine disruptor Benzyl Butyl Phthalate using Ozone and UV radiation. The model comprises four parallel sub-systems that are identified and isolated: (1) direct photolysis, (2) direct ozonation in the absence of hydroxyl radicals, (3) complete ozonation (direct + indirect oxidation) and (4) ozone + UV. To determine the nature of ozone attacks and the influence of ?OH radicals on O3 activity, two sets of experiments were performed: (i) Conventional ozonation and (ii) the same ozonation experiments in the presence of tert-butanol as radical scavenger, where only the reactions involving molecular ozone are present. The explored variables were: (i) Ozone concentration, (ii) Incident radiation rate at the reactor windows, (iii) reaction pH and (iv) the presence of radical scavengers. Major intermediates of BBP degradation were identified. Degradation kinetics was correctly modeled by a pseudo-second order kinetic model based on the sum of all the effects occurring during the treatment. The corresponding kinetic constants were obtained and the relative contributions of each of the considered subsystems were evaluated.